2022
DOI: 10.3389/fpls.2022.1064556
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a major QTL, Parth6.1 associated with parthenocarpic fruit development in slicing cucumber genotype, Pusa Parthenocarpic Cucumber-6

Abstract: Parthenocarpy is an extremely important trait that revolutionized the worldwide cultivation of cucumber under protected conditions. Pusa Parthenocarpic Cucumber-6 (PPC-6) is one of the important commercially cultivated varieties under protected conditions in India. Understanding the genetics of parthenocarpy, molecular mapping and the development of molecular markers closely associated with the trait will facilitate the introgression of parthenocarpic traits into non-conventional germplasm and elite varieties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…According to Pike and Peterson [7], this trait may be controlled by an incompletely dominant gene, P. The expression of the P gene in cucumber determines the occurrence of parthenocarpy, with plants that are homozygous dominant (PP) or heterozygous (Pp) expressing this gene and producing seedless fruits. Studies of two commercially cultivated parthenocarpic genotypes, PPC-6 and PPC-2, determined that a single incompletely dominant gene controls the trait of parthenocarpy, despite the significant influence of genetic background [8,9]. However, additional studies have indicated that the process of parthenocarpy in cucumber is quantitatively inherited and regulated by multiple genes [10][11][12][13][14].…”
Section: Cucumber (Cucumis Sativus L)mentioning
confidence: 99%
See 2 more Smart Citations
“…According to Pike and Peterson [7], this trait may be controlled by an incompletely dominant gene, P. The expression of the P gene in cucumber determines the occurrence of parthenocarpy, with plants that are homozygous dominant (PP) or heterozygous (Pp) expressing this gene and producing seedless fruits. Studies of two commercially cultivated parthenocarpic genotypes, PPC-6 and PPC-2, determined that a single incompletely dominant gene controls the trait of parthenocarpy, despite the significant influence of genetic background [8,9]. However, additional studies have indicated that the process of parthenocarpy in cucumber is quantitatively inherited and regulated by multiple genes [10][11][12][13][14].…”
Section: Cucumber (Cucumis Sativus L)mentioning
confidence: 99%
“…In the parthenocarpic PPC-6 genotype, a combination of QTL-seq analysis and conventional mapping with an F2:3 population revealed a major-effect QTL, Parth6.1, and two major-effect genes, Csa_6G396640 and Csa_6G405890. These genes are related to auxin biosynthesis and response factors, respectively [8]. Gou et al [2] evaluated the parthenocarpic ability of 201 cucumber germplasms through three independent experiments.…”
Section: Qtl Mapping and Identification Of Parthenocarpy Candidate Genesmentioning
confidence: 99%
See 1 more Smart Citation